2004
DOI: 10.1504/ijeh.2004.005866
|View full text |Cite
|
Sign up to set email alerts
|

E-procurement and automatic identification: enhancing supply chain management in the healthcare industry

Abstract: The concepts of automated e-procurement, or electronic B2B (business-to-business) trade, are grounded in the strategic leveraging of both tangible/intangible assets for successful implementation and execution of electronic trade, resulting in significant financial benefits for firms. Some of the major reasons for this growth include significant process savings from automation, compliance, and purchasing advantage; and reduced costs that organisations can experience by conducting transactions electronically. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…e-procurement strategies integrating automatic data identification and data capture (AIDC) technology and mobile devices could be used to effectively track pharmaceuticals throughout the supply chain and even for patient consumption of pharmaceutical products [28,29]. AIDC consists of a host of different technologies (e.g.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…e-procurement strategies integrating automatic data identification and data capture (AIDC) technology and mobile devices could be used to effectively track pharmaceuticals throughout the supply chain and even for patient consumption of pharmaceutical products [28,29]. AIDC consists of a host of different technologies (e.g.…”
Section: Perspectivesmentioning
confidence: 99%
“…Though key characteristics of e-procurement systems demonstrate how these systems can be used to increase transparency, enable automation, and integrate other forms of technology, arguably the most important function of an e-procurement system is its ability to generate cost-savings [29]. In fact, an e-procurement system's ability to reduce procurement costs is likely the single most important factor for medicines e-procurement systems adoption [28]. For example, a 2006 review of e-Health interventions in Romania found that e-procurement was used by the Ministry of Health for the acquisition of medicines for HIV/AIDS, tuberculosis, oncology, nephrology, diabetes, hematology, and psychiatry [30][31][32][33][34].…”
Section: Importance Of Cost-savings Generationmentioning
confidence: 99%
“…It has been highlighted that e-Procurement has to be evaluated in its complexity, which encompasses numerous goals: to rationalize expenditure, to reduce "administrative confusion" and costs, to foster operational efficiency (Croom, 2000), to strengthen organizations' network vision and technological collaboration with business partners (Gamble, 1999;Greenemeier, 2000;Murray, 2001), to completely automate certain procurement activities (Smith and Flanegin, 2004;Aisbett, Lasch and Pires, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Operational costs are growing while Capital investments have dried up. In the National Health Service (NHS) organisation, purchasing has been identified as one area whose immediate reform can quickly bring benefits (Newhouse, 1992;Smith and Flanegin, 2004;Congressional Budget Office, 2007). Alone, this is bound to fail unless new, innovative approaches to managing resources and novel supply chain practices are adopted.…”
Section: Introductionmentioning
confidence: 99%